Anti-aging quantum dot silicon dioxide as well as preparation method and application thereof
By preparing anti-aging quantum dot silica, using its quantum dot effect and oxygen deletion, the problem of insufficient anti-ultraviolet performance of nano-silicon dioxide is solved, and efficient anti-ultraviolet performance and material aging protection is achieved, providing green, Safe and environmentally friendly solutions.
Patent Information
- Application Number
- CN202411431759.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-07-31
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-07
AI Technical Summary
Nanosilica has poor UV resistance and cannot be used as an effective UV resistance additive. In addition, existing UV resistance agents such as nano zinc oxide and anatase titanium dioxide will cause organic materials to age or chemical reactions during use.
By preparing anti-aging quantum dot silica, using quantum dot effect and oxygen deletion, composite materials are formed to enhance UV resistance and anti-aging properties. Silica or silica acid and carbon sources are treated by vacuum furnace calcination to form particle size Aerobic deletion quantum dot silica is less than 20 nm and added to the substrate as an ultraviolet-proof agent or sprayed onto the surface.
It significantly improves the UV resistance, extends the service life of the material, and due to its non-toxicity and good inert stability, it avoids chemical reactions with the matrix or surrounding media, providing a green, safe and environmentally friendly solution.
Smart Images

Figure CN119263289A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of silicon dioxide materials, and in particular to anti-aging quantum dot silicon dioxide and a preparation method and application thereof. Background Art
[0002] Commonly used inorganic UV protection agents include nano zinc oxide and nano titanium dioxide. Nano titanium dioxide includes rutile titanium dioxide and anatase titanium dioxide. Rutile titanium dioxide mainly reflects ultraviolet rays and has poor UV protection performance. In addition to reflecting ultraviolet rays, anatase nano titanium dioxide also has good ultraviolet absorption function and has good UV protection function, but anatase titanium dioxide has extremely strong ultraviolet catalytic performance, which will decompose the organic matter in the matrix into CO2 and H2O, seriously reducing the service life of organic materials. Nano zinc oxide has both the function of absorbing and reflecting ultraviolet rays. Its disadvantage is that it is alkaline in water and easily reacts chemically with coatings and dyes. At the same time, nano zinc oxide will also react with acid during use, making zinc oxide ineffective and leaving holes, affecting the performance of the material.
[0003] Nano-silicon dioxide is non-toxic, extremely inert, does not react with the matrix, and has good stability during use. It is widely used as a material enhancer, toughener, thickener and other additives in rubber, plastic, coatings and skin care products. Studies have found that nano-silicon dioxide also has a certain ability to reflect ultraviolet rays, but overall, the anti-ultraviolet performance of nano-silicon dioxide is still insufficient, so it is rarely used directly as an anti-ultraviolet additive. Summary of the invention
[0004] In view of the problem that nano-silicon dioxide has poor UV protection performance and cannot be used as an anti-UV additive, the present invention provides an anti-aging quantum dot silica and a preparation method and application thereof, and utilizes the anti-UV and anti-aging properties of the composite synergistic material of the quantum dot effect and the oxygen vacancy effect. The anti-aging quantum dot silica of the present invention is added to a matrix or sprayed on the surface of the matrix, which can effectively block ultraviolet rays and thus prevent aging of the material.
[0005] In a first aspect, the present invention provides a method for preparing anti-aging quantum dot silica, wherein silica or silicic acid and a carbon source are calcined in a vacuum furnace in a first stage, the calcination temperature in the first stage is 300-750°C, and the calcination time in the first stage is 10 min-8 h, and then air is introduced for a second stage calcination, the calcination temperature in the second stage is 300-750°C, and the calcination time in the second stage is 10 min-8 h.
[0006] Furthermore, the carbon source is an organic carbon source or an inorganic carbon source. Preferably, the organic carbon source includes various resins, sugars and / or biomass, and the inorganic carbon source includes graphite, graphene, carbon nanotubes, activated carbon and / or carbon black.
[0007] Furthermore, the carbon source can be directly mixed with the finished silicon dioxide or finished silicic acid before use, or can be added during the preparation process of silicon dioxide or silicic acid.
[0008] Furthermore, silicon dioxide or silicic acid can be directly purchased from the market, or can be obtained by precipitation method, gas phase method, sol-gel method, hydrothermal method, microemulsion method, spray method or other known silicon dioxide or silicic acid preparation methods.
[0009] Among them, the precipitation method for preparing silicic acid is to add sodium silicate solution into an acid solution (such as hydrochloric acid, sulfuric acid, nitric acid, citric acid or oxalic acid, etc.) or a strong acid and weak base salt solution.
[0010] The gas phase method for preparing fumed silica is to react silicon halides or silane with oxygen.
[0011] The sol-gel method for preparing silicic acid is to mix ethyl silicate or other silicon-containing organic matter with distilled water, anhydrous ethanol and hydrochloric acid to form a sol, which is then dried and ground to form a gel after being allowed to stand.
[0012] Furthermore, the method further comprises post-processing the product obtained after calcination, wherein the post-processing comprises grinding, dispersing and / or drying.
[0013] In a second aspect, the present invention provides an anti-aging quantum dot silica obtained by the above-mentioned preparation method, wherein the oxygen vacancy content of the anti-aging quantum dot silica accounts for 0.0001 at.% to 15 at.% of the atomic percentage of oxygen element in the silica.
[0014] Furthermore, the particle size of the anti-aging quantum dot silica does not exceed 20 nm, preferably 1-20 nm.
[0015] In a third aspect, the present invention provides a use of the above-mentioned anti-aging quantum dot silica as an ultraviolet light blocking agent.
[0016] Furthermore, the dosage form of the UV protection agent is a concentrated slurry, powder or suspension spray.
[0017] Furthermore, when used, the anti-aging quantum dot silica is first dispersed by dry or wet ball milling; preferably, the dispersion time is 30 min to 20 h, and the ball mill is selected from a planetary ball mill, a vibrating ball mill or a drum ball mill.
[0018] Furthermore, the UV protection agent is added as an auxiliary agent in coatings, skin care products, cosmetics, colored aluminum, clothing, packaging, plastics, rubber, silica gel, dyes, toners, inks or pigments, or sprayed on the surface of a substrate.
[0019] Furthermore, the UV protection agent is used alone or in combination with white carbon black (silicon dioxide). White carbon black itself is a universal additive for organic materials. Mixing this product into white carbon black does not reduce the performance of the matrix, but can also improve the wear resistance, consistency, strength, dispersibility of other additives and other properties of the material, playing a role in multiple optimization of materials.
[0020] The beneficial effects of the present invention are: The present invention enhances the small size effect, surface interface effect and diffuse reflection and refraction of ultraviolet light by quantum dotting nano silicon dioxide. At the same time, the quantized silicon dioxide also has quantum size effect and macro quantum tunneling effect. Therefore, the anti-ultraviolet performance of quantum dot silicon dioxide is much higher than that of nano silicon dioxide with a particle size greater than 20 nm. On the one hand, oxygen vacancies are formed on the quantum dot silicon dioxide, and the oxygen vacancies are used to enhance the small size effect, surface interface effect and quantum tunneling effect, thereby increasing the diffuse reflection of ultraviolet light by the quantum dot silicon dioxide. On the other hand, the preparation method of the present invention can also form color centers on the quantum dot silicon dioxide that have an absorption and dissipation effect on ultraviolet light, thereby significantly improving the anti-ultraviolet ability of the quantum dot silicon dioxide.
[0021] The anti-aging quantum dot silica provided by the present invention is green, safe, non-toxic and environmentally friendly, has a simple production process, can be mass-produced and has low cost; it has strong UV protection capability and a wide UV protection wavelength range; after the anti-aging quantum dot silica is added to the paint, the fading of the paint is used as the basis for the UV aging of the paint, and the service life of the paint is extended by more than double; the anti-aging quantum dot silica of the present invention is an inorganic material, has good inertness, does not chemically react with oxygen, carbon dioxide and water in the air, and does not change its anti-aging performance after long-term placement, has no shelf life limit, does not chemically react with matrix organic matter or surrounding media during use, and has a long-lasting effect; the adding method of the anti-aging quantum dot silica of the present invention is simple, has excellent comprehensive effects and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0023] Figure 1 This is a transmission electron microscope image of the anti-aging quantum dot silicon dioxide prepared in Example 1.
[0024] Figure 2 yes Figure 1 The transmission electron microscope image corresponds to the electron diffraction pattern of the selected area.
[0025] Figure 3 This is the XPS spectrum of the anti-aging quantum dot silica prepared in Example 1.
[0026] Figure 4 It is the ultraviolet-visible light absorption spectrum of the quantum dot silica in Example 1, wherein curve a is the absorption spectrum of quantum dot silica without oxygen vacancies, and curve b is the absorption spectrum of anti-aging quantum dot silica. DETAILED DESCRIPTION
[0027] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0028] Unless otherwise specified, the oxygen vacancy ratios involved are the percentage of oxygen vacancies to the theoretical number of oxygen atoms in silicon dioxide.
[0029] Example 1 1. Preparation of silicic acid by precipitation method Sodium silicate was added to 500 mL of ethanol-water solution to prepare a sodium silicate-ethanol-water solution with a concentration of 0.40 mol / L, wherein the volume ratio of ethanol to water was 1:8. Then 100 mL of 0.2 mol / L nitric acid solution was prepared, and the nitric acid solution was slowly dripped into the sodium silicate-ethanol-water solution and stirred continuously until the titration end point pH=8.5 was reached, and a white flocculent precipitate was obtained. Then, the mixture was stirred continuously on a magnetic stirrer for 1 h and vacuum filtered to obtain a precipitate, which was washed nine times with deionized water and then once with anhydrous ethanol to remove impurity ions in the precipitate. The obtained precipitate was filtered and dried to obtain a white silicic acid powder.
[0030] (II) Preparation of anti-aging quantum dot silica 100 g of the obtained dried silicic acid was mixed with 100 g of an ethanol solution containing 20% of phenolic resin, dried, and then placed in a vacuum furnace for calcination at 600°C for 4 h to carbonize the phenolic resin and then reduce the silicon dioxide carbon. Air was introduced and the mixture was calcined at 600°C for 10 min. After the residual carbon was oxidized, the mixture was cooled in a vacuum and roller milled for 12 h to obtain oxygen-deficient quantum dot silicon dioxide powder with an average particle size of 12 nm, i.e., anti-aging quantum dot silicon dioxide. The powder morphology is as follows: Figure 1 shown.
[0031] (III) Material testing XPS test (such as Figure 3 As shown in the figure), the relative content of each element can be calculated based on the peak area and sensitivity factor of each characteristic peak in the spectrum, and the oxygen vacancy ratio of the obtained anti-aging quantum dot silica is 7 at.%.
[0032] The UV absorption performance of anti-aging quantum dot silica was measured using a UV-visible diffuse reflectance spectrometer. The experimental process was to place the sample to be tested in a sample tank, flatten it, and use BaSO4 powder as a standard white board to test the UV-visible diffuse reflectance absorption spectrum of the sample. At the same time, quantum dot silica with the same particle size and no oxygen vacancies obtained by calcining in air under the same calcination conditions (calcination temperature and calcination time) was used as a control. The results are shown in Figure 2. Figure 4 As shown, anti-aging quantum dot silica ( Figure 4 The absorbance of the ultraviolet absorption peak of the b curve in the figure is the absorbance of the quantum dot silica without oxygen vacancies ( Figure 4 The overall height and width of the absorption peak are also much higher than those of quantum dot silica without oxygen vacancies.
[0033] Anti-aging quantum dot silica and quantum dot silica without oxygen vacancies were added to blue marine alkyd paint at an addition amount of 20 wt.%, respectively. The aging test was carried out according to the relevant test standard (GB / T 14522-2008). After 30 days of the test, the color change of the coating during the aging process was tested with a WR-10 precision colorimeter. The color difference value of the blank group coating without adding silica was 19.0, the color difference value of the coating with the addition of quantum dot silica without oxygen vacancies was 14.1, and the color difference value of the coating with the addition of anti-aging quantum dot silica was 3.2.
[0034] Example 2 1. Preparation of a mixture of silicic acid and graphene Sodium silicate was added to 500 mL of ethanol aqueous solution to prepare a sodium silicate ethanol aqueous solution with a concentration of 0.40 mol / L, wherein the volume ratio of ethanol to water was 1:8. Then, graphene with a silicon-carbon atomic ratio of 5:1 was added to the sodium silicate ethanol aqueous solution, and the graphene and sodium silicate solution were mixed evenly by planetary ball milling to obtain an ethanol aqueous solution of sodium silicate and graphene.
[0035] Prepare 100 mL of 1 mol / L oxalic acid solution, slowly drip the oxalic acid solution into the ethanol aqueous solution of sodium silicate and graphene and continue stirring until the titration end point pH=8.5 is reached, and a white flocculent precipitate is obtained. Then continue stirring on a magnetic stirrer for 1 h and vacuum filter to obtain a precipitate, wash it nine times with deionized water and then wash it once with anhydrous ethanol to remove impurity ions in the precipitate. Filter the obtained precipitate and dry it to obtain a mixture of silicate and graphene.
[0036] (II) Preparation of anti-aging quantum dot silica The obtained dried mixture of silicic acid and graphene was placed in a vacuum furnace and calcined at 600°C for 3.5 h. Air was then introduced and the mixture was calcined at 600°C for 15 min to burn off the residual graphene. The mixture was cooled to room temperature in vacuum and subjected to planetary ball milling for 8.5 h to obtain oxygen-deficient quantum dot silica powder with an average particle size of 8 nm, i.e., anti-aging quantum dot silica.
[0037] (III) Material testing XPS detection showed that the oxygen vacancy ratio of the obtained anti-aging quantum dot silica was 7.4 at.%.
[0038] The ultraviolet absorption performance of the anti-aging quantum dot silica was measured by using an ultraviolet visible diffuse reflectance spectrometer, and the experimental process was the same as in Example 1. At the same time, quantum dot silica with the same particle size and no oxygen vacancies obtained by calcining in air under the same calcination conditions (calcination temperature and calcination time) was used as a control. The results show that the absorbance of the ultraviolet absorption peak of the anti-aging quantum dot silica is 5.1 times that of the quantum dot silica without oxygen vacancies, and the width of the absorption peak is also much higher than that of the quantum dot silica without oxygen vacancies.
[0039] Anti-aging quantum dot silica was added to a skin cream without sunscreen function (SPF value of 0) at an addition amount of 16 wt.%. The in vitro sun protection index test showed that the sun protection index (SPF value) of the blank group hand cream without silica was 16.8, and the sun protection index (SPF value) of the skin cream with anti-aging quantum dot silica was 124.3.
[0040] Although the present invention has been described in detail with reference to the accompanying drawings and in combination with the preferred embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, a person of ordinary skill in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions shall be within the scope of the present invention. Any person of ordinary skill in the art may easily think of changes or substitutions within the technical scope disclosed by the present invention, and these shall be within the scope of protection of the present invention.
Claims
1. A method for preparing anti-aging quantum dot silica, characterized in that: The silicon dioxide or silicic acid and the carbon source are calcined in a vacuum furnace in the first stage, the calcination temperature of the first stage is 300~750℃, and the calcination time of the first stage is 10 min~8 h. Then, air is introduced for the second stage calcination, the calcination temperature of the second stage is 300~750℃, and the calcination time of the second stage is 10 min~8 h.
2. The preparation method according to claim 1, characterized in that The carbon source is an organic carbon source or an inorganic carbon source.
3. The preparation method according to claim 1, characterized in that: The carbon source is directly mixed with the finished silica or silicic acid before use, or is added during the preparation of silica or silicic acid.
4. The preparation method according to claim 1, characterized in that: Silicon dioxide or silicic acid is a commercially available product purchased directly or prepared in-house.
5. An anti-aging quantum dot silica obtained by the preparation method according to any one of claims 1 to 4, characterized in that: The oxygen vacancy content of the anti-aging quantum dot silica accounts for 0.0001 at.% to 15 at.% of the atomic percentage of oxygen element in silica.
6. The anti-aging quantum dot silica according to claim 5, characterized in that The particle size of anti-aging quantum dot silica does not exceed 20 nm.
7. Use of the anti-aging quantum dot silica as claimed in claim 5 or 6 as an ultraviolet light blocking agent.
8. The use according to claim 7, characterized in that The dosage form of UV protection agent is concentrated slurry, powder or suspension spray.
9. The use according to claim 7, characterized in that UV protection agents are added as additives in coatings, skin care products, cosmetics, colored aluminum, clothing, packaging, plastics, rubber, silicone, dyes, toners, inks or pigments, or sprayed on the surface of the substrate.
10. The use according to claim 7, characterized in that The UV protection agent is used alone or in combination with white carbon black.